Code Mixing And Code Switching In Bumi Manusia Movie : Sociolinguistic Study - Ardya Budiarti, Mukie; Amalia Navi’ah, Risyda (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
``Bumi Manusia is a film set in the colonial era that introduces various languages that reflect the social and cultural conditions of Indonesian society. Therefore, this study aims to identify the types of code-mixing and code-switching in movies. This study uses qualitative research. Researchers also play a direct role in data collection by identifying data sources, listening to, and recording data. Based on the discussion of code mixing and code switching in the movie Bumi Manusia, the following conclusions can be drawn. First, when Indonesian and Javanese or Indonesian and Dutch are used, there is code mixing, which is used in the movie Bumi Manusia. This reflects everyday life in a mixed culture. Secondly, in the movie Bumi Manusia code switching is used where he uses three languages: Indonesian, Dutch and Javanese. This is because the background of the scenario depicts the colonial era of Wonokromo, a region near Surabaya in East Java. It also reflects cultural conflicts, status differences, and power differences that are achieved in the dialogue between characters.